2020
DOI: 10.1111/iwj.13329
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: Molecular mechanism whereby paraoxonase‐2 regulates coagulation activation through endothelial tissue factor in rat haemorrhagic shock model

Abstract: We investigated the molecular mechanism of paraoxonase‐2 (PON‐2) in regulating blood coagulation activation in rats with haemorrhagic shock through endothelial tissue factor (TF). Thirty adult Sprague Dawley rats were randomly divided into three groups: healthy control group (group A), the haemorrhagic shock PON‐2 treatment group (group B), and the haemorrhagic shock group (group C). After the model was established, blood was withdrawn from the inferior vena cava of all rats. The difference in plasma thrombomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Of relevance is a recent study suggesting a potential involvement of PON2 in the pathogenesis of venous thromboembolism in COVID-19 patients [125]. This is in line with previous but still recent studies showing that deregulated redox regulation in PON2 deficiency caused vascular inflammation and abnormalities in blood coagulation [126,127].…”
Section: Pon2 Role In Diseasessupporting
confidence: 81%
“…Of relevance is a recent study suggesting a potential involvement of PON2 in the pathogenesis of venous thromboembolism in COVID-19 patients [125]. This is in line with previous but still recent studies showing that deregulated redox regulation in PON2 deficiency caused vascular inflammation and abnormalities in blood coagulation [126,127].…”
Section: Pon2 Role In Diseasessupporting
confidence: 81%
“…Recent studies have shown that in endothelial cells, PON2 prevents systemic coagulation and inflammation by regulating the activity of tissue factors by a redox-dependent mechanism (Ebert et al 2018 ). In rats with hemorrhagic shock, it was found that under hypoxic and ischaemic conditions, PON2 regulates the expression of endothelial tissue-related genes such as plasma thrombomodulin transcription factors and endothelial tissue factor activating the mechanism of coagulation (Xu et al 2020 ).…”
Section: Role Of Pon2 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Egr-1 includes transactivation and repression regions, as well as three DNA-binding zinc finger regions that recognize GC-rich fragments of the promoter regions of target genes (51). Egr-1 has a wide range of functions, involving the control of synaptic plasticity, wound repair, inflammation, blood coagulation, pulmonary vascular permeability, growth and apoptosis of a number of cells (50,(52)(53)(54)(55)(56). Some findings suggest that Egr-1 can reverse the disease progression of acute myeloid leukemia by regulating changes in the downstream target genes c-myc and E2F1 (57).…”
Section: Discussionmentioning
confidence: 99%